SELAYANG PANDANG KETIMPANGAN GENDER DALAM BAHASA INDONESIA - * Jupriono (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2010)
Abstract. Some vocabulary and Indonesian phrases reflect that: a woman keeping a patient's life but a man being the lord of life; women always being the victims and blamed, and no comment toward man; men being common to be in charge of any position, accomplishment, organization, or job; it is, however, considered an optional " disorders " if women are in those place; females are subject to be identified and men are to give the identity.  Some Indonesian grammatical structures identify women as passive, and men are active. Vocabulary that connotes a man becomes a standard to refer to men and women. In institutional policies, it is clearly illustrated how women are still a source of a problem and are still far from being treated equally. Some expression reflects that the wife could earn / domiciled exceeds husband, but not recognized. Key words: gender inequality, vocabulary, expression, expression of identity, grammatical structures